Encapsulating lithium and sodium inside amorphous carbon nanotubes through gold-seeded growth. (December 2019) - Lan, Xiangna; Ye, Weibin; Zheng, Hongfei; Cheng, Yong; Zhang, Qiaobao; Peng, Dong-Liang; Wang, Ming-Sheng
Abstract: Metallic lithium promises the ultimate anode material for building next-generation Li batteries, though some fundamental hurdles remain unsolved. Li growth induced by hetero particles/atoms has recently emerged as a highly efficient route enabling spatial-control and dendrite-free Li deposition on anode hosts. However, the detailed mechanism of Li nucleation and its interaction with heterogeneous seeds are largely unknown. Herein, we investigate this issue by visualizing Au-seeded Li nucleation processes that guide Li deposition inside the one-dimensional hollow space of individual amorphous carbon nanotubes by in-situ transmission electron microscopy. A reversible two-step conversion process during Au–Li alloying/dealloying reactions is revealed, suggesting that the formation of Li3 Au plays the actual role in inducing Li nucleation. We propose a front-growth scenario to explain the spatially confined Li growth and stripping kinetic behaviors, which involves the mass addition and removal at the deposition front through ion diffusion along the tubular carbon shell. As a comparison, nanotubes without gold seeds inside exhibit uncontrolled dendrite-like Li growth outside the carbon shell. We further demonstrate that Au-seed growth can be successful in encapsulating sodium metal for the first time. These findings provide mechanistic insights into heterogeneous seeded Li/Na nucleation and space-confined deposition for design of high-performance battery anodes. Graphical abstract: We investigate the Au-seeded nucleation and space-confined deposition of lithium and sodium by visualizing these processes confined inside the one-dimensional hollow space of individual amorphous carbon nanotubes by in-situ TEM. A reversible two-step conversion process during Au–Li alloying/dealloying reactions is revealed, suggesting that the formation of Li3 Au plays the actual role in inducing Li nucleation. We also propose a front-growth scenario to explain the spatially confined Li growth and stripping kinetic behaviors. Image 1 Highlights: In-situ visualization of gold-seeded Li nucleation processes that enable Li to be encapsulated inside carbon nanotubes. A reversible two-step phase conversion process (Au-LiAu3 -Li3 Au) during Au–Li alloying/dealloying reactions is revealed. A new front-growth scenario is proposed to explain the spatially confined Li growth and stripping kinetic behaviors. The first demonstration of encapsulating sodium metal through heterogeneous seeded growth.